Effects of anthropogenic and ecological factors on Himalayan goral in Dhorpatan Hunting Reserve, Nepal - Hari Prasad Sharma; Sandeep Regmi; Bindu Pant; Jerrold L. Belant (Global Ecology and Conservation, 2023)
The Himalayan goral (Naemorhedus goral) is facing threats, such as habitat degradation and human disturbances, which are increasing. To aid their conservation, it is crucial to understand the anthropogenic and ecological factors that influence Himalayan goral occurrence. We conducted a study in Dhorpatan Hunting Reserve, Nepal using remote cameras to detect Himalayan gorals during late winter (March 2022) and spring (May 2022). Himalayan gorals were more likely to be detected in late winter (p = 0.253 ± 0.064) compared to spring (p = 0.187 ± 0.056) and the effects of anthropogenic and ecological factors on Himalayan gorals varied between these periods. During late winter, the distance to the nearest human settlement (βsettlement = 1.971 ± 1.147) and the number of other wild ungulates detected (βungulates = 2.954 ± 1.193) had a positive effect on Himalayan goral occurrence. In contrast, only the number of wild ungulate detections (βungulates = 3.262 ± 1.292) had a positive impact on Himalayan goral occupancy during spring. The number of livestock and carnivores detected during each season did not influence Himalayan goral occupancy. Our results highlight the importance of considering ecological and anthropogenic variables in understanding occupancy and distribution of Himalayan gorals to inform species conservation strategies.